Oral lichen planus versus oral lichenoid reaction: Difficulties in the diagnosis - Do Prado Renata; Marocchio Luciana; Felipini Renata (Wolters Kluwer Medknow Publications, 2009)
Lichen planus (LP) is a mucocutaneous disease with well-established clinical and microscopic features. The oral mucosa and skin may present clinical and microscopic alterations similar to those observed in LP, called lichenoid reactions (LRs), which are triggered by systemic or topical etiological agents. The difficulties faced to establish the differential diagnosis between the two pathologies were investigated in the literature. It was observed that the etiology of LP is still under discussion, with a tendency to self-immunity, while the etiology of LRs is related to the contact with specific agents, such as metallic restorative materials, resins, and drugs, allowing the establishment of a cause-effect relationship. In this case, the disease is caused by the antigen fixation in the epithelial cells, which are destructed by the immune system. Based on these data, protocols are suggested for this differentiation. The important role played by the integration between the clinician and the oral pathologist in the diagnostic process is highlighted. The treatment of LP comprises mainly the utilization of corticosteroids and the LR is treated by removal of the causal factor. Differentiation between the two diseases allows an effective and correct therapeutic approach.